The Abolition of Reconciliation through the Difference of Postmodernity - Chalvatzis, Spiros (Conatus - Journal of Philosophy, 2017)
The main goal of this article is to present perceptions of the world of two different and meaningfully promiscuous ways of thinking: from the one hand the perception formed during the contemporary times and from the other the perception formed during ‘’post-histoire’’. What has to be firstly clarified regarding the matter of post-modern is that it does not fight against its modern ancestor. Post in postmodernity does not mean the replacement of modernity. In other words, post is not connected with a time period that has passed and be replaced with something novel. The entirely analysis goes all the way based upon Derrida’s Thought. To be more specific that means that the goal is the signalization of the differences between modernity and postmodernity without a breath of identification, conciliation or concordant connections but through the percept of complementarity. It is also anticipated to be clarified a model of historic perspective, during its progression social configurations are structured after this model has been firstly approached through the prism of Rousseau’s thought.